Розробка інформаційно-пошукової системи каталогу заходів - Ольховський, І. В. (ХНУРЕ, 2019)
Features of the software development process are considered. The proposed method is convenient and fast for searching and filtering relevant activities and events. The urgency of this work is that at present the amount of information submitted in electronic form continues to grow exponentially, and therefore the question of efficient and fast search of the necessary information for today remains open. The aim of this work is to develop an information retrieval system in which multi-criteria search is implemented, which is based on the user's own interests. To solve this problem, the implementation of the information retrieval system as a catalog system was proposed, because such a system best meets the requirements.